(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2016)
This paper seeks to contextualize the frame by focusing on the formal properties of its specific medium (film). It looks outside of the frame’s function to think about it as a condition of its material. What defines the frame is that it is a product of its photographic condition: it is a direct result of the photochemical material and process (and is therefore contingent on processes of time and timing). Significantly, even in this ‘post-cinema’ climate, we are still conscious of the frame’s link to the medium of film. With this in mind, this paper proceeds to examine how digital formats (e.g. Red Digital Cinema Cameras, Apple Pro Res 422 HQ (Final Cut), and DNxHD (Avid)) appropriate the language that was once unique to the cinematic apparatus (e.g., frame, film gauge, frame rate, exposure) and argues that these terms do not adequately describe the processes by which digital cinema is produced and experienced. Fundamentally, this paper asks: what is so important about the frame? Is the very concept of the frame a defining feature of cinema?